ICT Enrichment Training Programme at Pusat Internet 1 Malaysia (PI1Ms) (poster) - Universiti Malaysia Sarawak, Institute Of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Poster exhibited at Karnival Pengajian Tinggi